A Comparative Study to Enhance Medication Adherence: Pillbox vs Medication Reminder Chart - Febriyanti, Alifia Putri; Tahar, Nurshalati; Badriani, Badriani; Dhuha, Nur Syamsi; Wahyudin, Munifah; Khaerani, Khaerani; Leboe, Dwi Wahyuni (Proceedings of International Pharmacy Ulul Albab Conference and Seminar (PLANAR); Vol 1 (2021): Proceedings of International Pharmacy Ulul Albab Conference and Seminar (PLANAR), 2021)
The main problems in geriatric patients with type 2 diabetes mellitus are polypharmacy and poor medication adherence, leading to increased morbidity and mortality. This study aims to compare the effectiveness of pillbox versus medication reminder charts in improving medication adherence among geriatric patients with Type 2 Diabetes Mellitus. The design of this study is an experimental, randomized controlled trial-pre test-post test control group design. The study subjects were geriatric patients with type 2 Diabetes Mellitus, conducted by random application technique. The study complied with all clinical research requirements by the Declaration of Helsinki. Ethics committee approval was obtained from UIN Alauddin Makassar. The instrument used in questionnaires to measure patients’ medication adherence using MMAS-8 and WHOQOL-BREEF to measure patients’ quality of life has been tested for validity and reliability. The result shows that pillbox can improve medication adherence (P=0,03) and improve quality of life (P=0,60); WHOQOL-BREEF questionnaire score of patients with pillbox intervention was increased 13.7619 while the WHOQOL-BREEF questionnaire score of patients with medication chart intervention was increased by 1.1402. The pillbox is the best tool in improving medication adherence and quality of life among geriatric patients with type 2 Diabetes Mellitus.